Peroxisome Proliferator-Activated Receptor γ Regulates the Expression of Lipid Phosphate Phosphohydrolase 1 in Human Vascular Endothelial Cells - Yazi Huang; Beilei Zhao; Yahan Liu; Nanping Wang (PPAR Research)
Lipid phosphate phosphohydrolase 1 (LPP1), a membrane ectophosphohydrolase regulating the availability of bioactive lipid phosphates, plays important roles in cellular signaling and physiological processes such as angiogenesis and endothelial migration. However, the regulated expression of LPP1 remains largely unknown. Here, we aimed to examine a role of peroxisome proliferator-activated receptor γ (PPARγ) in the transcriptional control of LPP1 gene expression. In human umbilical vein endothelial cells (HUVECs), quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) demonstrated that activation of PPARγ increased the mRNA level of LPP1. Chromatin immunoprecipitation assay showed that PPARγ binds to the putative PPAR-responsive elements (PPREs) within the 5′-flanking region of the human LPP1 gene. Genomic fragment containing 1.7-kilobase of the promoter region was cloned by using PCR. The luciferase reporter assays demonstrated that overexpression of PPARγ and rosiglitazone, a specific ligand for PPARγ, could significantly upregulate the reporter activity. However, site-directed mutagenesis of the PPRE motif abolished the induction. In conclusion, our results demonstrated that PPARγ transcriptionally activated the expression of LPP1 gene in ECs, suggesting a potential role of PPARγ in the metabolism of phospholipids.